Ecological Turn-around: Trends and Perspectives - Udo E. Simonis (Acta Prosperitatis, 2020)
This research focuses on the problem of large scale disproportion of success in the development of the banking sector and mostly unsuccessful development of the real sector of the economy. It should be noted that this disproportion is a subject of consideration in contemporary economic literature and our research is an attempt to broaden the issue and share ideas inside the international scientific circles. The main problem in the research is the impact of the banking sector's credit portfolio and the functioning of credit markets on the economic growth of the country. In this regard, it is very important to identify, study the macroeconomic stabilization and accelerated economic growth of the country and analyse the impact mechanisms of the credit market factors on economic growth. The conclusion that combines many of the research and opinions given in the survey can be as follows: From the economic point of view, the main function of banks is to increase the financing/lending of funds as the core point to increase investments in the economy. Thus, the development of the country in economic terms depends on the increase of investments. At present, it is in the hands of the banking sector whether to lead us to economic immobility or to accelerate the country's economic development through efficient allocation of resources.
Keywords: 330; banking sector; economic growth; GDP; credit booms